2015
DOI: 10.1002/ejic.201402918
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Bio‐Inspired Diiron Complexes and Their Catalytic Activity for Direct Hydroxylation of Aromatic Compounds

Abstract: Three [FeFe]‐hydrogenase model complexes [(μ‐dmedt){Fe(CO)3}2] [1; dmedt = SCH(CH3)CH(CH3)S], [(μ‐dmedt){Fe(CO)3}{Fe (CO)2PPh3}] (1‐PPh3), and [(μ‐dmest){Fe(CO)3}2] [1‐O; dmest = SCH(CH3)CH(CH3)S(O)], 1‐O were synthesized and characterized. These model complexes, which are generally used as the functional biomimics of the hydrogen‐producing dinuclear active site in [FeFe]‐hydrogenase, were used as efficient catalysts for the selective hydroxylation of aromatic compounds to phenols under mild conditions. Becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 63 publications
(52 reference statements)
1
38
0
Order By: Relevance
“…Hydrogenases, metalloenzymes that utilize iron, diiron or iron–nickel as metallic components, are able to perform reversible proton reduction at ambient temperature and pressure with activities, efficiencies, and overpotentials that are comparable to platinum . It is thus not surprising that chemists take inspiration from nature to mimic the active site of these metalloenzymes to develop new classes of proton reduction catalysts . Although several hundreds of hydrogenase model systems have been reported to date, most have been studied as homogeneous catalysts in organic solvents .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenases, metalloenzymes that utilize iron, diiron or iron–nickel as metallic components, are able to perform reversible proton reduction at ambient temperature and pressure with activities, efficiencies, and overpotentials that are comparable to platinum . It is thus not surprising that chemists take inspiration from nature to mimic the active site of these metalloenzymes to develop new classes of proton reduction catalysts . Although several hundreds of hydrogenase model systems have been reported to date, most have been studied as homogeneous catalysts in organic solvents .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure S1 , the IR spectra of the two complexes were measured in CH 2 Cl 2 solution, the IR spectra data between 2076 and 1900 cm −1 are characteristic of the carbonyl absorption peaks of these two compounds. Displacement of CO‐group of complex 1 by strong donating ligands of 2‐fluoropyridine and 3‐fluoropyridine to prepare complex 2 and 3 . Complexes 2 and 3 have a higher electron density compared with the all‐carbonyl parental [FeFe]‐hydrogenase model complex 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the study about the relationship between the reduction potential and complex structure is very meaningful. We chose the all‐carbonyl [FeFe]‐hydrogenase model complex (μ‐dmedt)Fe 2 (CO) 6 (dmedt=2,3‐butanedithiol) as the parent complex and introduced the structurally similar 2‐fluoropyridine and 3‐fluoropyridine ligands to synthesize two new [FeFe]‐hydrogenases model complexes 2 and 3 , respectively. A simple synthetic route of complexes 2 and 3 is shown in Scheme .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that phosphine ligands are good substitutes for the cyanide ligands found in the natural enzymes [10]. Recent studies on bridging dimethylethanedithiolate complexes have been reported in the literature [11,12], involving substitution of the parent complex [l-SCH(CH 3 )CH(CH 3 )S]Fe 2 (CO) 6 with PPh 3 or N-heterocyclic carbenes. The electrochemical properties and catalytic hydroxylation reactions of these complexes have also been studied.…”
Section: Introductionmentioning
confidence: 99%